PENGARUH KEPEMILIKAN PUBLIK, SOLVABILITAS DAN PROFITABILITAS TERHADAP AUDIT DELAY DENGAN REPUTASI KANTOR AKUNTAN PUBLIK SEBAGAI VARIABEL MODERATING - Riyan Tri Prakoso, Dewi Saptantinah Puji Astuti & Muhammad Rofiq Sunarko (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2017)
The purpose of this study was to analyze the significance of the influence of thePublic Ownership, Solvency, Profitability on the Audit Delay. It also tested themoderating variable (Public Accounting Firm Reputation) strengthening theinfluence of public ownership variables, Solvency and Profabilitas on the AuditDelay. This research was conducted at the state-owned company in BEI period 2011-2015 the number of samples used were 18 companies through purposive sampling.Data analysis technique used is the classical assumption, multiple linear regressionanalysis and Moderated Regression Analysis (MRA) with SPSS 22. The results ofpartial analysis we concluded that the independent variables did not significantlyinfluence the Audit Delay. The results showed that the moderating variableReputation Audit Firm does not moderate the Delay on the independent variable.While the results of simultaneous analysis we concluded that the independentvariable and significant effect on Audit Delay. The results of the analysis ofdetermination coefficient values obtained Adjusted R Square by 7.9% while theremaining 91.1% is influenced by other variables outside variables studied.Keywords: audit delay, public ownership, solvency, profitability, reputation publicaccounting firm.